2001
DOI: 10.1034/j.1600-0587.2001.240207.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the otter and the American mink in Białowieża Primeval Forest (Poland) compared to other Eurasian populations

Abstract: Diets of the otter Lutra lutra and the American mink Mustela vison were studied by scat analysis on five woodland rivers and streams in eastern Poland. Fish constituted 51% of food biomass consumed by otters in spring‐summer and 40% in autumn‐winter, with common fish (perch Perca fluviatilis, pike Esox lucius, and roach Rutilus rutilus) being captured most frequently by the otters. Amphibians (mainly Rana temporaria, which also dominated in the living community) made up 34% of otters’ food biomass in spring‐su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
191
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(222 citation statements)
references
References 41 publications
18
191
2
11
Order By: Relevance
“…Obviously, to enable these ecological adaptations the otter is flexible in its feeding habits (Brzeziński et al 1993, Carss 1995, Lanszki and Körmendi 1996, Jędrzejewska et al 2001, Clavero et al 2003. Although there is no doubt that the otter is a piscivorous (Chanin 1981, Lanszki and Molnár 2003, Brzeziński et al 2006, it is characterized by flexibility in the type of prey caught (Lanszki et al 1999).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Obviously, to enable these ecological adaptations the otter is flexible in its feeding habits (Brzeziński et al 1993, Carss 1995, Lanszki and Körmendi 1996, Jędrzejewska et al 2001, Clavero et al 2003. Although there is no doubt that the otter is a piscivorous (Chanin 1981, Lanszki and Molnár 2003, Brzeziński et al 2006, it is characterized by flexibility in the type of prey caught (Lanszki et al 1999).…”
mentioning
confidence: 99%
“…Moreover, river size, water discharge and riparian vegetation cover can influence the composition of the diet of otters. As an example, Jędrzejewska et al (2001) reported that the river type can affect the quantity of amphibians in its diet. Furthermore, the alteration of riparian habitats is often accompanied by the reduction of fish biomass, forcing otters to forage upon alternative prey (Weber 1990, Lanszki et al 1999, Clavero et al 2003.…”
mentioning
confidence: 99%
See 3 more Smart Citations